Integrating Local Culture in English Language Teaching: Enhancing authentic materials and cultural awareness - Miqawati, Alfi Hidayatu; Wijayanti, Fitri; Intan Purnama, Aisah (Journal of English in Academic and Professional Communication, 2024)
This study aims to discuss one of the local cultures in the form of dance and its integration in English language learning in an effort to preserve the local culture and promote students' cultural awareness. The research design deployed was descriptive qualitative. Two art practitioners served as the subjects of the study and the data were obtained through an interview process. The data were analyzed using four steps data collection, data reduction, data presentation, and drawing conclusions. In addition, library study was also used to understand and study theories from various literature or sources related to the study. The findings showed that Lahbako Dance tells the story of the tobacco processing process starting from harvesting to packaging. In its development, the dance is modified because of the need for innovation and adaptation to developments and promoting its sustainability. In language teaching, its success depends on the use of teaching materials that accurately reflect authentic language use and cultural settings. Lahbako Dance can be inserted into the teaching and learning activities as an authentic material that can promote students' language skills, motivation, and cultural awareness. By doing so, local culture can also be well-preserved. Further studies related to the developments of other authentic materials are suggested.